The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1161/01.cir.60.4.752
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemodynamic effects of cigarette smoking in man assessed by systolic time intervals and echocardiography.

Abstract: SUMMARY Sixteen healthy subjects, ages 18-35 years, were studied in the supine position by means of systolic time intervals and echocardiography before and after smoking a high-nicotine cigarette (2.5 mg nicotine) and a tobacco cigarette of very low nicotine content (< 0.02 mg nicotine) to assess and compare the immediate effects upon left ventricular function.Smokers (n = 12) and nonsmokers (n = 4) behaved alike. High-and low-nicotine cigarettes both caused significant increases in heart rate, systolic and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…Though it has been known that smoking and alcohol predispose to heart failure, [28,29] our data showed no correlation of the above two epidemiological variables with the disease condition. The low percentage of smokers and alcoholics in DCM clearly reß ects a subset of DCMs that are secondary to certain systemic disorders.…”
Section: Epidemiological Analysiscontrasting
confidence: 77%
“…Though it has been known that smoking and alcohol predispose to heart failure, [28,29] our data showed no correlation of the above two epidemiological variables with the disease condition. The low percentage of smokers and alcoholics in DCM clearly reß ects a subset of DCMs that are secondary to certain systemic disorders.…”
Section: Epidemiological Analysiscontrasting
confidence: 77%
“…Cigarette smoking increases heart rate and blood pressure, both principal determinants of myocardial oxygen consumption 14. Goldbarg et al showed in healthy individuals that the left ventricular stroke index decreased significantly at several levels of exercise after smoking, although there was no significant change at rest 15.…”
Section: Precipitating Factors For Relapse Of Congestive Heart Failurementioning
confidence: 99%
“…The cardiovascular effect of cigarette smoking has been reported by many investigators [9][10][11]. They ob served that cigarette smoking has an acute effect upon the circulation, including an increase in both HR and BP, although it may have a different effect with long-term exposure [12], Moreover, these effects were mainly relat ed to the amount of tobacco smoked, the habits of inhal ing the smoke and the type of tobacco.…”
Section: Discussionmentioning
confidence: 98%